Comparison of oxidative stress and the frequency of polymorphisms in the HFE gene between hemoglobin S trait blood donors and sickle cell disease patients - Viana-Baracioli, L. M. S. [UNESP]; Tukamoto Junior, N. C. [UNESP]; Ricci Junior, O.; Mattos, L. C.; Angulo, I. L.; Bonini-Domingos, C. R. [UNESP] (Funpec-editora, 2011)
It is well documented that Hb S and iron affect blood cells, and trigger oxidative processes and generation of free radicals with potential for lipid peroxidation. We evaluated the frequency of polymorphisms in the HFE gene in Hb AS blood donors and how these polymorphisms influenced lipid peroxidation and antioxidant capacity. Blood samples were collected from 211 Hb AS blood donors, 119 Hb AA blood donors as a control group, and 28 sickle cell disease patients (Hb SS). The H63D allele was found at a frequency of 10.5% in the Hb AS samples, and the C282Y allele frequency was 0.7%. In the control group, the frequencies of the H63D and C282Y alleles were 13.4 and 2.1%, respectively. In the sickle-cell disease patients, the H63D and the C282Y allele frequencies were 10.7 and 3.5%, respectively. The frequencies of the C282Y and H63D polymorphisms in Hb AS blood donors are similar to those reported for the Brazilian population. Serum malondialdehyde values, indicative of lipid peroxidation, were highest in sickle cell patients, independent of the polymorphisms in the HFE gene, with significant differences, showing the influence of Hb S allele in the levels of lipid peroxidation. However, the trolox equivalent antioxidant capacity average levels, indicative of the antioxidant capacity, were reduced with significant differences, indicating that in spite of a lipid peroxidation raise, this is not followed by the increased of the antioxidant capacity, leading to oxidative stress.
Keywords: Hemoglobinopathy; Hemoglobin S; Antioxidant capacity; HFE; Hemochromatosis